THE ROLE OF CONTROL IN THE TEACHING PROCESS AND ITS FORMS OF ORGANIZATION - Azizova Makharam Rashitovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The role of control in the educational process and the forms of its organization help to remove the educational process in an efficient and orderly form. These forms provide teachers with the necessary resources to increase accountability, manage student production and learning, collect data and assessments, and produce and evaluate student achievement, and other important controls.